2, 2'-Dipyridylamine: A tripod ligand enabling practical access to diaryl ethers via Cu-catalyzed coupling reaction. Issue 22 (17th November 2022) - Chen, Yuanguang; Xu, Huashen; Chen, Lu; Hou, Anyuan; Chen, Guoliang
Abstract: 2, 2'-dipyridylamine (DPA) is hereby firstly reported as a novel and efficient tridentate ligand for promoting copper(I)-catalyzed C-O/S coupling reactions of abundant aryl bromines with related phenols or thiophenols. The key to this very discovery is the identification of an N -donor tripod ligand (DPA), and such a reaction allows the conversion of simple starting materials to complex diaryl ethers or diaryl thioethers, which are important synthetic intermediates in the preparation of bioactive molecules. Graphical Abstract: UF0001